Characterization of the complete chloroplast genome of Farfugium japonicum (Asteraceae). Issue 2 (1st February 2021) - Gu, Ye; Ma, Qing; Lu, Yin
Abstract: The complete chloroplast genome of Farfugium japonicum, which belongs to tribe Senecioneae (Asteraceae) was characterized. The size of the chloroplast genome is 151, 222 bp in length with a large single copy (LSC) of 83, 417 bp, a small single copy (SSC) of 18, 125 bp, and a pair of inverted repeats of 24, 840 bp. The chloroplast genome encodes a set of 133 genes, including 88 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenomic analysis based on chloroplast genomes of 18 related species revealed that F. japonicum is clustered with species from Ligularia and rooted with the other Senecioneae genus. The chloroplast genome of Farfugium japonicum provides an important resource for further study of molecular evolution.